Regional brain patterns of dopamine, metabolites and D2 receptors in memory - Galkina, Olga V.; Podgornaya, Elena K. (Pharmacology, biochemistry and behavior, 1996)
Patterns of dopamine (DA), 3,4-dihydroxyphenyl acetic (DOPAC), and homovanillic (HVA) acids, para-tyramine (p-TA), and D2 receptors for eleven structures of forebrain and midbrain were examined at 1 and 6 days after one trial passive avoidance training of rats, at 1 day after "psychogenic" amnesia production, immediately following training, and at the last day after foot shock of rats with previous "psychogenic" amnesia administration. Essential dopaminergic differences have been found between the groups studied. More significant neurochemical changes were observed in rats from trained and retrieval training groups. Regional DA changes were accompanied by a diminution of DA metabolism, an increase of D2 receptor density and p-TA. These neurochemical alterations differentially characterized the regional neurochemical patterns found in rat's exhibition nonretention (trained), forgetting, and amnesia. It is suggested that the present data reflect the existence of quantitative relationships between D2 receptors, DA, and p-TA, which are probably important in modulation of memory.